2022
DOI: 10.1039/d1nj04647k
|View full text |Cite
|
Sign up to set email alerts
|

A peptidomimetic-based thixotropic organogel showing syneresis-induced anti-adhesion against water and ice

Abstract: The self-assembly, organogelation, syneresis, and anti-adhesion properties of a Peptidomimeticcontaining L-phenylalanine and 2,6-dimethylpyridine 3,5-dicarboxylic acid have been studied in detail. The peptidomimetic forms a transparent gel in aromatic solvents such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This is a typical characteristic of gels with a high degree of crosslinks. 51 , 54 Strong gels with G ′ > 3000 Pa could be obtained at the polymer content of 15∼23 wt%, including the limonene gel by PPeOx 10 - b -POx1 6 ( Figure S14 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a typical characteristic of gels with a high degree of crosslinks. 51 , 54 Strong gels with G ′ > 3000 Pa could be obtained at the polymer content of 15∼23 wt%, including the limonene gel by PPeOx 10 - b -POx1 6 ( Figure S14 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the G ′ values are several times up to about one order of magnitude higher than G ″ values over the whole frequency range (ω = 0.01–100 rad s –1 ). This is a typical characteristic of gels with a high degree of crosslinks. , Strong gels with G ′ > 3000 Pa could be obtained at the polymer content of 15∼23 wt%, including the limonene gel by PPeOx 10 - b -POx1 6 (Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…When the shrunken gel is cooled back, it swells again and the hydrogel reforms. Gumtya et al have shown that the gels of compound P ( Figure 54 a) in aromatic solvents, such as benzene, toluene, xylene, dichlorobenzene, are stable at room temperature, but exhibit syneresis when they are cooled at 15 °C [ 126 ].…”
Section: Syneresismentioning
confidence: 99%